PERBEDAAN WAKTU KONTAK KARBON AKTIF DALAM MENURUNKAN KADAR AMONIA PADA LIMBAH CAIR PENYAMAKAN KULIT DI PT. XYZ (Jurnal Kesehatan Siliwangi, 2021)
The liquid waste produced by leather tanning has a very pungent odor that comes from the ammonia content in it. The results of the laboratory examination of the quality of liquid waste produced by chemical leather tanning gave 7.72 mg/L of ammonia. Those amount of ammonia did not meet the standard quality in accordance with the regulation on Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia No 21 Tahun 2018 about Water Quality Standard Waste for business and/or tanning industry activities, which regulate the amount of Ammonia (NH3-N) should be no more than 2 mg/L. This study aims to determine the average of percentage and efficiency of reducing ammonia levels using adsorbents. The research is using a quasi-experimental research design with Pretest – Posttest with Control, From the results of the study, it was found that the average percentage of reduction in ammonia levels by 20 minute contact time was 30.44%, by 30 minute contact time was 61.73%, andby 40 minute contact time was 85.98%. So it can be concluded that the most effective contact time to reduces the ammonia level on liquid waste of leather tanning production is 40 minutes contact time with activated carbon which reduces to the level of 1.08 mg/L amount of ammonia and has met the standard quality.